Industri Ekonomi Syariah di Indonesia dan Inggris - Mallika Nurwin Fitria; Mauliddina Kurnia Dewi (Tadabbur: Jurnal Integrasi Keilmuan, 2022)
The development of the Islamic economy in Indonesia is progressing very rapidly. This is inseparable from several driving factors, both internally and externally. As for Britain as a country with many ethnicities, including Muslims, it has proven the success of the principle of interest-free banking which was initially unacceptable in the West and answered the negative views of economists on Islamic banks. So that at this time the UK became the center of Islamic finance in Europe. This paper aims to describe the development of the sharia economic industry in Indonesia as a Muslim-majority country and in England as a representation of a country that is currently developing its sharia economy as a result of the large number of Muslim ethnic groups in the country. This paper is important because it looks at the potential, challenges, and strategies for developing Islamic economics in the two countries. The method used in this paper is descriptive qualitative with literature study, namely collecting various supporting literature and analyzing it so that it becomes important information in sharia economic studies.